2011
DOI: 10.1007/s10495-011-0630-0
|View full text |Cite
|
Sign up to set email alerts
|

Review: milk fat globule-EGF factor 8 expression, function and plausible signal transduction in resolving inflammation

Abstract: Although the cloning and molecular characterization of MFG-E8 was first reported in the early 90s, breakthrough on MFG-E8 research came into light when it was explored as an outstanding factor for phagocytosis of apoptotic cells by professional macrophages in 2002. Since then numerous studies have been performed on MFG-E8 not only to demonstrate the role of phagocytic clearance of apoptotic cells, but also to focus on a wide range of aspects, even emphasizing on a direct link to innate-immune systems. In terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
166
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(175 citation statements)
references
References 56 publications
5
166
0
Order By: Relevance
“…The reason why D89E, but not ANX V, can efficiently block PtdSer-dependent viral entry is still not clear. Since the ligands of MFG-E8 and TIM receptors are well studied and the common ligand of TIM receptors and MFG-E8 is only PtdSer (54,82,83), it is unlikely that D89E conceals an unidentified molecule(s) that also plays a role in virus binding via MFG-E8 and TIM-1 and -4. One possible explanation is that D89E can completely conceal exposed PtdSer on the viral envelope, while ANX V cannot due to its different access to PtdSer upon binding.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why D89E, but not ANX V, can efficiently block PtdSer-dependent viral entry is still not clear. Since the ligands of MFG-E8 and TIM receptors are well studied and the common ligand of TIM receptors and MFG-E8 is only PtdSer (54,82,83), it is unlikely that D89E conceals an unidentified molecule(s) that also plays a role in virus binding via MFG-E8 and TIM-1 and -4. One possible explanation is that D89E can completely conceal exposed PtdSer on the viral envelope, while ANX V cannot due to its different access to PtdSer upon binding.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-derived MFG-E8 -Although MFG-E8 is expressed in many tissues and cells, its expression in prostate cancer cell lines has remained unknown (31). To determine whether MFG-E8 is expressed in prostate cancer cells, protein was collected and analyzed from RAW 264.7 macrophages and three different prostate cancer cell lines: a prostate cancer murine-derived cell line, RM-1, and two bone metastatic human-derived cell lines, PC-3 and C42B (Fig.…”
Section: Mfg-e8 Expression In Macrophages Andmentioning
confidence: 99%
“…One explanation for this observation is that post-lactational efferocytosis promotes breast tumor malignancy through production of wound healing cytokines, which are known to drive breast cancer growth and invasion. In support of this idea, MFG-E8 [203] and its receptor v 3/5, as well as Gas6 and its ligand MerTK [116,204] are frequently overexpressed in breast cancers. One recent study demonstrated that the protumorigenic cytokine IL-6 induces expression of MerTK, enhancing the ability of macrophages to engulf apoptotic cells and increasing production of wound healing cytokines such as IL-4 and IL-10 [205].…”
Section: Physiological and Pathological Consequences Of Efferocytosismentioning
confidence: 84%